Archaeological finds from the cave of Ciganska jama near Kočevje from the period after the Ice Age - Velušček, Anton (Arheološki vestnik, 2011)
The article primarily presents the Holocene archaeological finds from the cave of Ciganska jama, the most important Gravettian station in Slovenia, which is part of the Željnske jame system of water active caves. Pottery prevails among the finds. It has been divided into prehistoric pottery, which is the subject of the detailed analysis, and pottery from the historical periods. The analysis reveals that Ciganska jama served as an occasional shelter for humans also in three periods of younger prehistory: at the time of the Sava group, the Lasinja culture, and the horizon of pottery with furrowed incisions (HKBV). The tunnel near Stranska jama (which is part of the Željnske jame cave system) could also have been a necropolis, a grave or a sacral area, the age of which, regardless of the fact that the finds point to the Neolithic-Eneolithic, cannot be defined in detail without radiometric dating of the human skull fragment.